Green Human Resource Management (Green HRM) in the Era of Digital Transformation and Future Research Potential: A Bibliometric Analysis (20152025) - Sipayung, Maurits Sahata (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to map the development and research trends of Green Human Resource Management (GHRM) in the context of digital transformation and sustainability using a bibliometric analysis approach of 1,219 scientific articles published between 2015 and 2025. Data were collected from Scopus, Google Scholar, and CrossRef and analyzed using VOSviewer to identify publication trends, dominant keywords, author collaboration networks, and main thematic clusters. The results indicate a significant rise in publications since 2020, driven by growing global attention to the Sustainable Development Goals (SDGs) and accelerated organizational digitalization. Cluster analysis revealed five major research themes: organizational sustainability and green performance context, green values and behavioral drivers, psychological climate and innovation, green HRM practices and sustainability, and green HRM, CSR, and responsible leadership. Furthermore, seven future research directions are proposed, including the integration of GHRM with Artificial Intelligence, Big Data Analytics, and sector-specific applications such as SMEs, forestry, mining, and tourism. This study concludes that GHRM plays a strategic role in advancing global sustainability agendas in the Industry 5.0 era, where the synergy between digital innovation, green HR policies, and SDG-oriented strategies will become the foundation for sustainable organizational performance.